Problematyka programów nauczania religii w szkole powszechnej i gimnazjum ogólnokształcącym na łamach „Miesięcznika Katechetycznego i Wychowawczego” w latach 1932-1939 - Ceglarek, Roman (Poznańskie Studia Teologiczne, 2017)
The educational changes launched in Poland in 1932 included the establishment of new types of schools, such as seven-year common schools and four-year middle schools. Therefore, there was a need for school curricula that would correspond to the new educational system. The National Board of Education first prepared the preliminary drafts and subsequently passed the school curricula. The Catechetic and Pedagogical Monthly analyzed them over the span of the 1930s. Not only the analyses and their results were published in the magazine, but also the contents of the curricula. That is why in pre-war Poland this Catholic periodical became one of the most important information sources on school curricula of religious education. Moreover, it was a source from which successive syllabuses were derived.